2018
DOI: 10.1111/sode.12336
|View full text |Cite
|
Sign up to set email alerts
|

Emotion understanding and maternal sensitivity as protective factors against hostile attribution bias in anger‐prone children

Abstract: The present research examined children’s anger proneness, emotion understanding, and maternal sensitivity during toddlerhood as predictors of children’s hostile attribution bias (HAB) during the later preschool years. At 2.8 years (N = 128), maternal sensitivity (e.g., child‐centered behavior) was observed during mother–child play and snack, and parents reported on children’s anger proneness. At 3.3 years, emotion understanding (i.e., ability to identify emotional expressions accurately) was measured via an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…An alternative explanation is that children with poor emotion understanding discourage parents from talking about emotions, either indirectly (e.g., the child does not respond to the parent’s efforts) or directly (e.g., the child actively refuses to talk about emotions). In kindergarten, externalizing behavior problems might exacerbate poor child emotion understanding through a process of peer rejection and lack of socialization in peer groups (Di Giunta, Pastorelli, Thartori, Bombi, Baumgartner, Fabes & Enders, 2018; Racz, Putnick, Suwalsky, Hendricks & Bornstein, 2017; Viana, Zambrana, Karevold & Pons, 2019; Wong, Chen & McElwain, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is that children with poor emotion understanding discourage parents from talking about emotions, either indirectly (e.g., the child does not respond to the parent’s efforts) or directly (e.g., the child actively refuses to talk about emotions). In kindergarten, externalizing behavior problems might exacerbate poor child emotion understanding through a process of peer rejection and lack of socialization in peer groups (Di Giunta, Pastorelli, Thartori, Bombi, Baumgartner, Fabes & Enders, 2018; Racz, Putnick, Suwalsky, Hendricks & Bornstein, 2017; Viana, Zambrana, Karevold & Pons, 2019; Wong, Chen & McElwain, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among forensic psychiatric inpatients with psychotic disorders, the HAB was not associated with theory of mind (Bratton, O'Rourke, Tansey, & Hutton, 2017). Wong et al (2019) found that an interaction between a child's anger proneness and emotion understanding was predictive of the HAB when there were low levels of emotion understanding (r = 0.56).…”
Section: Emotionmentioning
confidence: 96%
“…Moreover, high levels of maternal sensitivity (e.g. appropriate responses to children's requests) were associated with low levels of the HAB in children (r = 0.55; Wong, Chen, & McElwain, 2019). Children with a disorganized attachment style showed higher levels of the HAB and more aggressive goals relative to children with an organized attachment style (Zajac, Bookhout, Hubbard, Carlson, & Dozier, 2018).…”
Section: Peers and Parentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Anger proneness is a key characteristic of early temperamental difficulty; poor self-control is typically associated with deficient regulation of angry emotions; angry emotions often elicit parental power-assertive control, which then almost certainly elicits children's further anger and resentment. Finally, poorly regulated anger is associated with hostile attributional biases (Wong, Chen, & McElwain, 2019) and with resentful, hostile traits-some of the central characteristics of low Agreeableness.…”
Section: Discussionmentioning
confidence: 99%